Synthesis and Biological Evaluation of Lactimidomycin and Its Analogues. Issue 52 (18th November 2015) - Larsen, Brian J.; Sun, Zhankui; Lachacz, Eric; Khomutnyk, Yaroslav; Soellner, Matthew B.; Nagorny, Pavel
Abstract: The studies culminating in the total synthesis of the glutarimide‐containing eukaryote translation elongation inhibitor lactimidomycin are described. The optimized synthetic route features a Zn II ‐mediated intramolecular Horner–Wadsworth–Emmons (HWE) reaction resulting in a highly stereoselective formation of the strained 12‐membered macrolactone of lactimidomycin on a 423 mg scale. The presence of the E, Z ‐diene functionality was found to be key for effective macrocyclizations as a complete removal of these unsaturation units resulted in exclusive formation of the dimer rather than monocyclic enoate. The synthetic route features a late‐stage installation of the glutarimide functionality via an asymmetric catalytic Mukaiyama aldol reaction, which allows for a quick generation of lactimidomycin homolog 55 containing two additional carbons in the glutarimide side chain. Similar to lactimidomycin, this analog was found to possess cytotoxicity against MDA‐MB‐231 breast cancer cells (GI50 =1–3 μM) using in vitro 2D and 3D assays. Although lactimidomycin was found to be the most potent compound in terms of anticancer activity, 55 as well as truncated analogues 50 –52 lacking the glutarimide side‐chain were found to be significantly less toxic against human mammary epithelial cells. Abstract : Culminated effort : The total synthesis and in vitro biological studies of glutarimide‐containing eukaryote translation elongation inhibitor lactimidomycin and its extended chain analogue are described.